Reduction in mortality risk with opioid agonist therapy: a systematic review and meta‐analysis. (18th September 2019) - Bahji, A.; Cheng, B.; Gray, S.; Stuart, H.
Abstract : Introduction: Opioid agonist therapies are effective medications that can greatly improve the quality of life of individuals with opioid use disorder. However, there is significant uncertainty about the risks of cause‐specific mortality in and out of treatment. Objective: This systematic review and meta‐analysis explored the association between methadone and buprenorphine with cause‐specific mortality among opioid‐dependent persons. Methods: We searched six online databases to identify relevant cohort studies, calculating all‐cause and overdose‐specific mortality rates during periods in and out of treatment. We pooled mortality estimates using multivariate random effects meta‐analysis of the crude mortality rate per 1000 person‐years of follow‐up as well as relative risks comparing mortality in vs. out of treatment. Results: A total of 32 cohort studies (representing 150 235 participants, 805 423.6 person‐years, and 9112 deaths) met eligibility criteria. Crude mortality rates were substantially higher among methadone cohorts than buprenorphine cohorts. Relative risk reduction was substantially higher with methadone relative to buprenorphine when time in‐treatment was compared to time out‐of‐treatment. Furthermore, the greatest mortality reduction was conferred during the first 4 weeks of treatment. Mortality estimates were substantially heterogeneous and varied significantly by country, region, and by the nature of the treatment provider. Conclusion: Precautions are necessary for the safer implementation of opioid agonist therapy, including baseline assessments of opioid tolerance, ongoing monitoring during the induction period, education of patients about the risk of overdose, and coordination within healthcare services.